PENGARUH LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA DI KANTOR CAMAT TELUK DALAM KABUPATEN NIAS SELATAN - Duha, Maeria (Universitas Nias Raya, 2025)
The purpose of this research is to determine the influence of the work environment on work motivation at the Telukdalam Subdistrict Office, South Nias Regency. This type of research is quantitative. The data source for this research is from employees using a questionnaire, with the population and sample for this research being 33 respondents. The data analysis method used is multiple regression analysis. Based on the results of hypothesis testing research with a value of tcount 4.148>ttable 1.696, the researchers concluded that there is an influence of the work environment on work motivation at the Telukdalam Subdistrict Office, South Nias Regency. The suggestion of this research is that to increase employee work motivation, organizations need to create a conducive environment so that they feel comfortable doing their work. And the working atmosphere needs to be improved in accordance with employee wishes in order to increase employee work motivation.